Ionic regulation ability in Rutilus frisii kutum fingerlings during sea water adaptation. - Hossein, Seyedali; Saad, Che Roos; Bourani, Mohammad Sayyad; Mohd. Daud, Hassan; Zokaei Far, Hadi; Harmin, Sharr Azni (Academic Journals, 2011)
Experiments were conducted to determine the effects of weight on the ionic regulation ability of reared Rutilus frisii kutum fingerlings during adaptation to the seawater and downstream migration. Accordingly, the ionic regulation ability of Cl-, K+, Na+ and Mg2+ in kutum fingerlings with weights of 1, 3, 5 and 7 g in three different salinities, that is 13‰ (the Caspian Sea salinity), 7‰ (estuarine area) and fresh water (as control, 0.3-0.5‰), were assessed. The blood samples were provided before being transferred as control (fresh water) and during adaptation to the sea and estuary water in a period of up to 336 h by a pooling method. The measurements of ions were carried out for blood serum Na+ and K+ and alsoplasma Cl-1 and Mg2+ by photometric methods. This investigation showed that ionic regulatory ability of kutum fingerlings depends on their weights. Results of ionic changes during the duration of 336 h (14 days) proved that unlike kutum fingerling with weights of 3, 5 and 7 g, the ionic regulation system in 1 g fingerlings were not able to expel excess ions. Further 1 g kutum were not physiologically ready (smolt) for downstream migration.